Seafood Allergy in Asia: Geographical Specificity and Beyond - Wai, Christine Y. Y.; Leung, Nicki Y. H.; Leung, Agnes S. Y.; Wong, Gary W. K.; Leung, Ting F. (Frontiers in Allergy, 2021)
Asian countries have unique ways of food processing and dietary habits that may explain the observed differences in the prevalence, natural history, epidemiology and sensitization pattern of food allergic diseases when compared to western countries. Per capita consumption of seafood, including fish and shellfish, is well above the global average for many Asian countries because of their coastal geographical location and rich seafood supply. The wide availability and high abundance of seafood in Asian countries have shaped a diverse way of processing and eating this major food group. Such unique features have significant impact on the sensitization profile and allergenicity of Asians to fish and shellfish. For example, fish and shellfish are eaten raw in some countries that may promote sensitization to heat-labile allergens not otherwise seen in other regions. Fermented fish sauce is commonly used as a condiment in some countries which may promote fish sensitization. Shrimp head and shrimp roe are regarded as delicacies in some countries, but their allergen profiles are yet to be characterized. Freshwater fish and shellfish are a common food source in many Asian countries but the allergenicity of many such species remains unknown. In this review, we discuss factors that may contribute to differences in molecular profile and sensitization pattern for fish and shellfish that are observed in Asian populations and revisit the current status of seafood allergy in this part of the world. Acknowledging the similarities and differences of seafood allergy patterns between Asian and western populations can help us refine a better strategy for diagnosing and managing seafood allergy.